Police transport of firearm-injured patients—more often and more injured. Issue 1 (July 2021) - Maher, Zoё; Beard, Jessica H.; Dauer, Elizabeth; Carroll, Madeleine; Forman, Steven; Topper, Gena V.; Pathak, Abhijit; Santora, Thomas A.; Sjoholm, Lars Ola; Zhao, Huaqing; Goldberg, Amy J.
Abstract : BACKGROUND: Police transport (PT) of penetrating trauma patients decreases the time between injury and trauma center arrival. Our study objective was to characterize trends in the rate of PT and its impact on mortality. We hypothesized that PT is increasing and that these patients are more injured. METHODS: We conducted a single-center, retrospective cohort study of adult (≥18 years) patients presenting with gunshot wounds (GSWs) to a level 1 center from 2012 to 2018. Patients transported by police or ambulance (emergency medical service [EMS]) were included. The association between mode of transport (PT vs. EMS) and mortality was evaluated using χ 2, t tests, Mann-Whitney U tests, and logistic regression. RESULTS: Of 2, 007 patients, there were 1, 357 PT patients and 650 EMS patients. Overall in-hospital mortality was 23.7%. The rate of GSW patients arriving by PT increased from 48.9% to 78.5% over the study period ( p < 0.001). Compared with EMS patients, PT patients were sicker on presentation with lower initial systolic blood pressure (98 vs. 110, p < 0.001), higher Injury Severity Score (median [interquartile range], 10 [2–75] vs. 9 [1–17]; p < 0.001) and more bullet wounds (3.5 vs. 2.9, p < 0.001). Police-transported patients more frequently underwent resuscitative thoracotomy (19.2% vs. 10.0%, p < 0.001) and immediate surgical exploration (31.3% vs. 22.6%, p < 0.001). There was no difference in adjusted in-hospital mortality between transport groups. Of patients surviving to discharge, PT patients had higher Injury Severity Score (9.6 vs. 8.3, p = 0.004) and lower systolic blood pressure on arrival (126 vs. 130, p = 0.013) than EMS patients. CONCLUSION: Police transport of GSW patients is increasing at our urban level 1 center. Compared with EMS patients, PT patients are more severely injured but have similar in-hospital mortality. Further study is necessary to understand the impact of PT on outcomes in specific subsets in penetrating trauma patients. LEVEL OF EVIDENCE: Epidemiological, level III.